Komitmen Organisasi Karyawan Outsourcing Kabupaten Kudus Ditinjau dari Stress Kerja - Mahardayani, Iranita Hervi; Dhania, Dhini Rama (Universitas Ahmad Dahlan, 2014)
ABSTRACTThis study aims to determine empirically the relationship between job stress and organizational commitment on outsourced employees in Kudus. The population in this study were outsourced employees in Kudus and the samples were 200 outsourced employees that were selected by accidental sampling technique. Job stress scale and organizational commitment scale were used to collect the data and the result was analyzed using the product moment correlation that was calculated by SPSS 15.0 for windows. The results showed that there was a significant negative relationship between job stress and organizational commitment (r = - 0.648, p <0.01).Keywords : Commitment organization, outsourcing, stress work